Lyme Disease and Associated NMDAR Encephalitis: A Case Report and Literature Review - Natalja Predkele; Jānis Mednieks (MDPI AG, 2021)
We present a case of a patient with positive N-methyl-D-aspartate receptor (NMDAR) IgG antibodies in their serum and cerebrospinal fluid (CSF) associated with neuroborreliosis. Clinically, the patient presented with symptoms of confusion, as well as behavioral and speech impairments. Regardless of antibacterial treatment, no significant improvement was achieved. Methylprednisolone provided a marked improvement in the patient's clinical signs and CSF findings. The screening did not reveal any underlying neoplasm. Taking into account the marked clinical improvement after treatment with glucocorticosteroids, we suggest that NMDAR encephalitis is a possible autoimmune complication in neuroborreliosis patients requiring additional immunotherapy.